2012
DOI: 10.1075/ijcl.17.3.01pot
|View full text |Cite
|
Sign up to set email alerts
|

Does semantic tagging identify cultural change in British and American English?

Abstract: This paper explores the viability of automated semantic tagging as a tool of cultural analysis comparing American and British English using the Brown family of corpora. Pairs of corpora representing written language production from circa 1961, 1991 and 2006 were contrasted by comparing key semantic tags. This method was then evaluated in relation to three earlier studies which attempted to uncover cultural differences via assigning keywords to ad hoc categories. After outlining the differences found, we conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 12 publications
0
20
1
2
Order By: Relevance
“…The three semantic tags with the highest negative log likelihood values in the MELC-US vs. MELC-UK comparison appear in Table . INSERT TABLE 2 ABOUT HERE The underuse of Z6: NEGATIVE in MELC-US is due to the overuse of items such as not, n't and no in MELC-UK. This difference is not, however, limited to our data, as other studies have found that British English is generally characterised by a greater use of words expressing negativity and uncertainty than American English (Leech and Fallon, 1992;Potts and Baker, 2012).…”
Section: Insert Table 1 About Herecontrasting
confidence: 44%
See 1 more Smart Citation
“…The three semantic tags with the highest negative log likelihood values in the MELC-US vs. MELC-UK comparison appear in Table . INSERT TABLE 2 ABOUT HERE The underuse of Z6: NEGATIVE in MELC-US is due to the overuse of items such as not, n't and no in MELC-UK. This difference is not, however, limited to our data, as other studies have found that British English is generally characterised by a greater use of words expressing negativity and uncertainty than American English (Leech and Fallon, 1992;Potts and Baker, 2012).…”
Section: Insert Table 1 About Herecontrasting
confidence: 44%
“…an American tendency to talk about the military, weaponry and technology, contrasted to a British focus on time and modality; see Potts and Baker, 2012). Nor has the analysis revealed dramatic contrasts reflecting differences in healthcare systems.…”
Section: Rasing the Profile Of The Typical Cancer Victim (Melc-uk)mentioning
confidence: 99%
“…For the purpose of this study, phrasal verbs were defined as any two-part verbs consisting of a lexical verb followed (continuously or discontinuously) by an adverbial particle, which "behaves to some extent either lexically or syntactically as a single verb" (Quirk et al 1985(Quirk et al : 1150. However, the concordances automatically generated by WordSmith Tools included not only phrasal verbs but also verb + particle free combinations and verb + prepositional phrases since many particles function as both adverbs and prepositions.…”
Section: Methodsmentioning
confidence: 99%
“…The nearest neighbour classifier (e.g. Manning et al 2008), for example, requires a set of known samples (prototypes) from particular classes from which it builds a set of features (e.g. words for text classification).…”
Section: Text Prototype Selection Methodsmentioning
confidence: 99%